The Effectiveness of Post-Exercise Sports Massage on Recovery in U17 Football Athletes at the Thirteens Football Academy - Nasrul; Yati Ruhyati; Syam Hardwis (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to examine the effectiveness of post-exercise sports massage in accelerating Countermovement Jump (CMJ) performance recovery in U17 football athletes at the Thirteens Football Academy. The research employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. Thirty U17 football athletes participated in the study and received a post-exercise sports massage intervention lasting 15–20 minutes using effleurage and petrissage techniques. CMJ performance was measured before and after the intervention. Data were analyzed using descriptive statistics and a paired samples t-test. The results showed an increase in the mean CMJ score from 44.67 before treatment to 50.83 after treatment, with a mean difference of –6.167. The paired samples t-test revealed a significant difference between pre- and post-treatment scores (t = –5.651; p < 0.05), indicating that sports massage had a significant effect on improving CMJ performance recovery. These findings suggest that post-exercise sports massage is an effective recovery method to enhance lower limb explosive power in young football athletes and may be considered as part of structured recovery programs in football academies.